Dancing at home and abroad. - Cleveland, C. H., Jr. (Boston, O. Ditson & Co., 1878)
Cleveland's manual opens with an interesting account of the building blocks required for setting up a successful private dancing academy. He includes discussion on the architectural requirements, music, progress of students, hours and division of classes, dealing with children, and how to manage balls. The second part of the manual covers "fashionable dances," and the author describes quadrilles, the "Boston Waltz," and twenty-nine figures for the German (also known as cotillon), a group dance comprised of a series of party games.
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Ballroom dancing -- Handbooks, manuals, etc; Dance; Dance schools; Dance Instruction and Physical Culture